TRPC6 channel translocation into phagosomal membrane augments phagosomal function - Riazanski, Vladimir (2015)
Defects in the innate immune system in the lung with attendant bacterial infections contribute to lung tissue damage, respiratory insufficiency, and ultimately death in the pathogenesis of cystic fibrosis (CF). Professional phagocytes, including alveolar macrophages (AMs), have specialized pathways that ensure efficient killing of pathogens in phagosomes. Phagosomal acidification facilitates the optimal functioning of degradative enzymes, ultimately contributing to bacterial killing. Generation of low organellar pH is primarily driven by the V-ATPases, proton pumps that use cytoplasmic ATP to load H(+) into the organelle. Critical to phagosomal acidification are various channels derived from the plasma membrane, including the anion channel cystic fibrosis transmembrane conductance regulator, which shunt the transmembrane potential generated by movement of protons. Here we show that the transient receptor potential canonical-6 (TRPC6) calcium-permeable channel in the AM also functions to shunt the transmembrane potential generated by proton pumping and is capable of restoring microbicidal function to compromised AMs in CF and enhancement of function in non-CF cells. TRPC6 channel activity is enhanced via translocation to the cell surface (and then ultimately to the phagosome during phagocytosis) in response to G-protein signaling activated by the small molecule (R)-roscovitine and its derivatives. These data show that enhancing vesicular insertion of the TRPC6 channel to the plasma membrane may represent a general mechanism for restoring phagosome activity in conditions, where it is lost or impaired.